Maternal and perinatal outcomes in early versus late onset pre-eclampsia – A comparative study - Nirmita Saha; Sandip Sarkar; Rupali Modak; Lipika Adhikari; Debdatta Ghosh (Asian Journal of Medical Sciences, 2025)
Background: Hypertensive disorders are the most common medical complications of pregnancy and complicate up to 10% of pregnancies. Aims and Objectives: This prospective study examined the effects of early-onset pre-eclampsia (EO-PE) and late-onset pre-eclampsia (LO-PE) on composite maternal and perinatal outcomes. Materials and Methods: Pregnant women booked, unbooked or referred having pre-eclampsia admitted in Department of Obstetrics and Gynaecology at RG Kar Medical College and Hospital from march 2023 to february 2024 were included in the study. Results: The most common complications were eclampsia (16.7% vs. 13.3%; P=0.609), HELLP syndrome (P=0.018), and abruptio placentae (21.7% vs. 6.7%; P=0.018). Although all these complications were more in the EO-PE group, the difference did not gain statistical significance. EO-PE is more strongly linked to small for gestational age births, stillbirths, and birth asphyxia. Conclusion: LO-PE was more prevalent among primigravida patients. The adverse maternal outcomes were more in mothers of the EO-PE group than the LO-PE group but in most cases, the difference did not reach statistical significance. Adverse neonatal complications were significantly more common in EO-PE.